2017
DOI: 10.1016/j.biochi.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The expanding repertoire of G4 DNA structures

Abstract: The definition of DNA and RNA G-quadruplexes (G4s) has recently been broadened to include structures with certain defects: bulges, G-vacancies or mismatches. Despite the striking progress in computational methods for assessing G4 folding propensity, predicting G4s with defects remains problematic, reflecting the enhanced sequential diversity of these motifs. "Imperfect" G4 motifs, i.e., those containing interrupted or truncated G-runs, are typically omitted from genomic analyses. We report here studies of G4s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 46 publications
1
61
0
2
Order By: Relevance
“…However, in spite of some attempts, the stability and folding topology of G4‐DNA and G4‐RNA are difficult to predict purely on the basis of sequence information . A growing body of structural and biophysical data demonstrates that these structures frequently escape the consensus motif (i.e., G n ‐N i ‐G n ‐N j ‐G n ‐N k ‐G n , in which n= 2 to 4; i , j , k =1 to 7; and N=any base), as evidenced by snap‐back, G‐vacant, and bulged G4 structures which are difficult to predict by bioinformatics algorithms . In this context, experimental probing of formation and topology of G4 structures, both in vitro and in the cellular environment, is crucial for understanding of their persistence and biological roles, as well as for improvement of bioinformatics algorithms …”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of some attempts, the stability and folding topology of G4‐DNA and G4‐RNA are difficult to predict purely on the basis of sequence information . A growing body of structural and biophysical data demonstrates that these structures frequently escape the consensus motif (i.e., G n ‐N i ‐G n ‐N j ‐G n ‐N k ‐G n , in which n= 2 to 4; i , j , k =1 to 7; and N=any base), as evidenced by snap‐back, G‐vacant, and bulged G4 structures which are difficult to predict by bioinformatics algorithms . In this context, experimental probing of formation and topology of G4 structures, both in vitro and in the cellular environment, is crucial for understanding of their persistence and biological roles, as well as for improvement of bioinformatics algorithms …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified DNA folds in human cells, in the human genome. They are now a part of a growing family of diverse noncanonical DNA folds . Although the identification of DNA folds in the human genome is only relatively recent, the list of implicated diseases is still being elucidated—but is already growing.…”
Section: What Is New and Conclusionmentioning
confidence: 99%
“…Non-Watson-Crick secondary structures of nucleic acids, and in particular, G4 structures in DNA is an area of extremely active research (12)(13)(14)(15)(16). Although G4 structures were initially described in the context of telomeres, recent genomic data revealed tens of thousands of sequences throughout the genome (14,17) that, in principle, could form G4 structures, called potential G-quadruplex-forming sequences (PQS).…”
mentioning
confidence: 99%
“…Given the abundance of PQS in the promoter regions throughout the genome (12,13), the generality of the proposed mechanism may be very likely. Supporting this view is the fact that Fleming et al also provide a more comprehensive mechanistic explanation for the DNA oxidation and BER-dependent transcriptional activation reported in several cellular studies (4,10,11,21).…”
mentioning
confidence: 99%